ANALISIS KETAHANAN PELUNASAN ANGSURAN KOPERASI SIMPAN PINJAM MENGGUNAKAN PENDEKATAN SURVIVAL ANALISIS - Hakim, Lukmanul; Aprianti, Yuli (Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2025)
This study aims to analyze the repayment durability of cooperative loan installments and to identify factors influencing default risk. The study applies survival analysis using the Kaplan–Meier estimator and Cox Proportional Hazard regression. Secondary data were obtained from Tunggal Karya Semamung Savings and Loan Cooperative, Sumbawa Regency, covering January–October 2025, with a sample of 147 cooperative members. The dependent variable is repayment durability, while independent variables include loan size, business scale, and loan status. Kaplan–Meier results indicate a decreasing survival probability over time. Cox regression results reveal that loan size has a positive and significant effect on default risk, whereas business scale has a negative and significant effect. Loan status does not show a statistically significant effect. These findings suggest that economic capacity and loan characteristics play a crucial role in determining loan repayment sustainability in cooperative financing